Tuning the electrochemical potential of perfunctionalized dodecaborate clusters through vertex differentiation - Wixtrom, Alex I. (Chem Commun (Camb), 2018)
We report a new class of redox-active vertex-differentiated dodecaborate clusters featuring pentafluoroaryl groups. These [B(12)(OR)(11)NO(2)] clusters share several unique photophysical properties with their [B(12)(OR)(12)] analogues, while exhibiting significantly higher (+0.5 V) redox potentials. This work describes the synthesis, characterization, and isolation of [B(12)(O-CH(2)C(6)F(5))(11)NO(2)] clusters in all 3 oxidation states (dianion, radical, and neutral). Reactivity to post-functionalization with thiol species via S(N)Ar on the pentafluoroaryl groups is also demonstated.